Q: What is 2b 3b simplified?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

The equation (b2 - 2b) + (3b - 6) = b2 + b - 6

3b/4.5 = 2b/3

The given terms can be simplified to: a -b

A + 2B cannot be simplified.

Related questions

It is: b -8 when simplified

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

It is: b+4 when simplified

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

It is: B+2b when simplified assuming B and b have different values

By collecting like terms and so it is a-3b-1 when simplified

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

The equation (b2 - 2b) + (3b - 6) = b2 + b - 6

2B means they hit a double 3B means they hit a triple

3b/4.5 = 2b/3

The given terms can be simplified to: a -b